A Cheap Mesoporous Silica from Fly Ash as an Outstanding Adsorbent for Sulfate in Water - Pizarro-Konczak, J; Ortiz-Calderon, C; Castillo-Castillo, X (Elsevier B.V., 2018)
This research describes the development of a very cheap mesoporous silica material similar to hexagonal mesoporous silica (HMS) and using a silicate extract as precursor. This precursor is obtained from cheap fly ash by an easy calcination process at 850 °C and a green extraction with water. The obtained mesoporous fly ash material had a surface area of 282 m2 g−1 and a pore size of 5.7 nm. It was functionalized with ethylene diamino moieties via the well-known SAMMS method, followed by a DRIFT analysis that clearly showed the successful functionalization. An excellent adsorbent was obtained for the adsorption of sulfate anions by the solid s modification with copper forming a copper-ethylenediamine complex. The adsorption of sulfates was studied in a batch system where the pH at highest adsorption 8 was and the adsorption time remarkably fast (5 min). The kinetic data were fitted according to a pseudo-second order model with a high coefficient of linear regression at different initial concentrations. The adsorption isotherm that best fitted the experimental data was the Freundlich model. The maximum sulfate adsorption capacity of this very cheap fly ash based adsorbent was 146.1 mg g−1, 3 times greater than the values reported in literature and commercial adsorbent materials. © 2018